Bioactive Flavonoids and Catechols as Hif1 and Nrf2 Protein Stabilizers - Implications for Parkinson’s Disease - Smirnova, Natalya A. (Aging Dis, 2016)
Flavonoids are known to trigger the intrinsic genetic adaptive programs to hypoxic or oxidative stress via estrogen receptor engagement or upstream kinase activation. To reveal specific structural requirements for direct stabilization of the transcription factors responsible for triggering the antihypoxic and antioxidant programs, we studied flavones, isoflavones and catechols including dihydroxybenzoate, didox, levodopa, and nordihydroguaiaretic acid (NDGA), using novel luciferase-based reporters specific for the first step in HIF1 or Nrf2 protein stabilization. Distinct structural requirements for either transcription factor stabilization have been found: as expected, these requirements for activation of HIF ODD-luc reporter correlate with in silico binding to HIF prolyl hydroxylase. By contrast, stabilization of Nrf2 requires the presence of 3,4-dihydroxy- (catechol) groups. Thus, only some but not all flavonoids are direct activators of the hypoxic and antioxidant genetic programs. NDGA from the Creosote bush resembles the best flavonoids in their ability to directly stabilize HIF1 and Nrf2 and is superior with respect to LOX inhibition thus favoring this compound over others. Given much higher bioavailability and stability of NDGA than any flavonoid, NDGA has been tested in a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-animal model of Parkinson’s Disease and demonstrated neuroprotective effects.